Sublingual Misoprostol versus Foley catheter for cervical ripening in women with preeclampsia or gestational hypertension: A randomized control trial - Sedigheh Ayati; Elahe Hasanzadeh; Leila Pourali; Mohammadtaghi Shakeri; Atiye Vatanchi (Shahid Sadoughi University of Medical Sciences, 2019)
Background Delivery is the only definite cure for hypertensive disorders. Therefore, cervical ripening and labor induction are important to achieve favorable outcomes. Objective This Randomized Control Trial (RCT) is aimed to compare the effects of sublingual misoprostol and Foley catheter in cervical ripening and labor induction among patients with preeclampsia or gestational hypertension. Materials and Methods A total number of 144 women with preeclampsia or gestational hypertention with indication of pregnancy termination, who were referred to academic hospitals of the University of Medical Sciences in Mashhad, Iran, between March 2015 and December 2016, were randomly divided into two groups. In group one (n = 72), 25 µg of misoprostol tablet was administrated sublingually every 4 hr up to six doses. In group two (n = 72), a 16F Foley catheter was placed through the internal cervical os, inflated with 60 cc of sterile saline. Results There were no significant differences between groups regarding the demographic characteristics, primary bishop score, and pregnancy termination indication. The cervical ripening time (primary outcome) (8.2 vs 14.2 hr, p < 0.00), induction to delivery interval (15.5 vs 19.9 hr, p < 0.00), and vaginal delivery before 24 hr (63.9% vs 40%, p = 0.03) were significantly different between the two groups. There was no significant difference between groups in view of oxytocin requirement (p = 0.12), neonatal Apgar score (p = 0.84), or neonatal intensive care unit admission (p = 78). Conclusion This trial showed that the application of sublingual misoprostol, compared to the Foley catheter, can reduce cervical ripening period and other parameters related to the duration of vaginal delivery. This misoprostol regimen showed inconsiderable maternal complications.